MASCULINITIES: COMPLEXITIES AND VARIATIONS - Duncan, Norman (PINS-Psychology in Society, 2025)
Shefer, T, Ratele, K, Strebel, A, Shabalala, N & Buikema, R (eds) (2007) From boys to men: Social constructions of masculinity in contemporary society. Lansdowne: University of Cape Town Press/Juta. ISBN 978-1-91989-503-1. Pages xiii + 280.